Serotonergic modulation of orbitofrontal activity and its relevance for decision making and impulsivity. Issue 3 (11th November 2016) - Mavrogiorgou, Paraskevi; Enzi, Björn; Klimm, Ann‐Kristin; Köhler, Elke; Roser, Patrik; Norra, Christine; Juckel, Georg
Abstract: Background: The orbitofrontal cortex seems to play a crucial role in reward‐guided learning and decision making, especially for impulsive choice procedures including delayed reward discounting. The central serotonergic system is closely involved in the regulation of impulsivity, but how the serotonergic firing rate and release, best investigated by the loudness dependence of auditory evoked potentials (LDAEP), interact with orbitofrontal activity is still unknown. Methods: Twenty healthy volunteers (11 males, 9 females, 31.3 ± 10.6 years old) were studied in a 3T MRI scanner (Philips, Hamburg, Germany) during a delay discounting task, after their LDAEP was recorded using a 32 electrodes EEG machine (Brain Products, Munich, Germany). Results: Significant positive correlations were only found between the LDAEP and the medial orbitofrontal part of the superior frontal gyrus (SFG/MO) [Δ immediate reward – delayed reward] for the right ( r = 0.519; P = 0.019) and left side ( r = 0.478; P = 0.033). This relationship was stronger for females compared with males. Orbitofrontal activity was also related to the Barratt Impulsivity Scale. Conclusions: This study revealed that low serotonergic activity as measured by a strong LDAEP was related to a high fMRI signal intensity of SFG/MO during immediate reward behavior which is related to impulsivity. Since this relationship was only found for the infralimbic medial and not for the middle or lateral part of the orbitofrontal cortex, an exclusive projection tract of the serotonergic system to this cortical region can be assumed to regulate impulsive reward‐orientated decision making. Hum Brain Mapp 38:1507–1517, 2017 . © 2016 Wiley Periodicals, Inc.